MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN 1 SAMPAI 10 MELALUI MEDIA KALUNG BERANGKA PADA ANAK TUNAGRAHITA RINGAN - Rosnita - - (Jurnal Penelitian Pendidikan Khusus, 2012)
Against the background of this research by the findings in the field, where the class D 1 C in SLB  Luak Nan Bungsu in which there are two children Tunagrahita mild and one teacher. When carried out to know the symbol numbers of learning, children can not recognize the symbol numbers 1 to 10 visible when performed tests in which the states and show the symbol numbers 1 to 10 children experiencing difficulties. Based on this, the researchers tried to use the media framed necklace to enhance the ability to know the symbol numbers 1 to 10. This research improved learning using action research methods class (Classroom Action Research) conducted in collaboration with colleagues. Data were collected through observation and testing techniques, and then analyzed qualitatively and quantitatively. The results showed that 1) enhance the learning process to know the symbol numbers 1 to 10 through the media framed necklace done in two cycles. I conducted six times a cycle of meetings and the second cycle with five meetings. Each cycle of meetings were held with the planning, implementation, observation and reflection. 2) The symbol of learning to know numbers by stating and showing the symbol numbers 1 to 10 through the media necklace dates to the early tests the ability of FJ (30%) and FT (10%). I cycle to increase the ability of the child: FJ (60%) and FT (55%). While growing up the second cycle FJ gain (85%) and FT (80%) of about 20 items tested. Thus, it can be concluded that through the media framed necklace can enhance the ability to recognize the symbol numbers 1 to 10 minor children Tunagrahita D1 class C in SLB Luak Nan Bungsu. It is recommended to schools, teachers and researchers can use the media next to the necklace framed in learning to know the symbol numbers 1 to 10 children Tunagrahita light.